PERKEMBANGAN KURIKULUM PAI DI INDONESIA - Ahmad Dhaifi (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2017)
This research study exhaustively regarding owth of curriculum in Indonesia. This research aim to to know how far growth of curriculum in Indonesia start from pra-independenting till now. This research use book study method. Data collecting conducted with documentation study technique. Result of this research show growth of curriculum in Indonesia at education domain specially very signifikan, come up with curriculum 2013 (K-13) very orienting at realizing education with character, creating education with vision of local and also create education which is pure and fraternize.